Achieving high permeability of in-situ formed lightweight Cf/SiC(rGO)px/SiC porous ceramics with improved interfacial compatibility for transpiration cooling. Issue 13 (October 2022) - Huang, Zhenguo; Hu, Jiahao; Huang, Wenyan; Zhuang, Kun; Zheng, Yinong; Li, Ke; Jin, Chao; Wang, Yufeng; Xue, Zhichao; Liang, Jiahao; Yao, Rongqian
Abstract: Making lightweight porous ceramics with excellent permeability applied for transpiration cooling is still challenging. Herein, an ingenious fabrication method is proposed to successfully prepare Cf /SiC(rGO)p x /SiC porous ceramics possessing low density, high permeability and satisfactory mechanical properties. The introduction of carbon fibers for constructing channels and SiC(rGO)p with three-dimensional (3D) honeycomb cellular net-like structure, could effectively decrease density and improve porosity. Meanwhile, self-supporting porous skeleton, high open porosity and uniform pores distribution contribute to brilliant permeability of the products. Good interfacial compatibility among SiC(rGO)p, carbon fibers and β-SiC/SiO x C y /Cfree matrix, as well as toughening effects of carbon fibers are beneficial for enhancing fracture toughness and compressive strength. Particularly, Cf /SiC(rGO)p0.6 /SiC porous ceramics exhibit low density (1.12 g·cm −3 ), low linear shrinkage (3.22%), especially high permeability (1.36 ×10 −7 mm 2 ), satisfactory fracture toughness (1.77 MPa·m 1/2 ), excellent hardness (3.88 GPa) and compressive strength (6.41 MPa), focusing on potential applications as coolant medium in transpiration cooling. Highlights: Lightweight Cf /SiC(rGO)p x /SiC porous ceramics were ingeniously fabricated. Introduction of SiC(rGO)p with unique structure could effectively improve porosity. Permeability reaches up to 1.36 × 10 −7 mm 2, in a relatively high level. Improved interfacial compatibility benefits the mechanical properties. Practical applications in transpiration cooling can be adequately considered.